Improving Students’ Speaking Skills Through Ventriloquist Dolls at the Eighth Grade of SMP Generasi Bangsa - Anggraini, Risa; Hasibuan, Syahsyabila (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study aims to determine whether the implementation of ventriloquist dolls can significantly improve students’ speaking skills. The subjects were eighth-grade students of SMP Generasi Bangsa Medan in the 2024/2025 academic year. This study was conducted using the Classroom Action Research (CAR) method. Two types of data were collected, quantitative and qualitative. Quantitative data were obtained through speaking tests, while qualitative data were collected through interviews, classroom observations, diary notes, and documentation. Based on the findings from the quantitative data, students’ speaking skills improved significantly, as indicated by the increase in their mean scores, from 57.24 in the pre-test to 68.56 in the post-test of Cycle I, and 82.8 in the post-test of Cycle II. Furthermore, the researchers found that the use of ventriloquist dolls made students enjoy the class more because the dolls’ characters attracted their attention and increased their enthusiasm for storytelling, thereby enhancing their speaking skills. Teachers also get new ways of teaching that are not boring and effective in helping students speak.